2021
DOI: 10.1002/hep4.1621
|View full text |Cite
|
Sign up to set email alerts
|

How Do Patients With Cirrhosis and Their Caregivers Learn About and Manage Their Health? A Review and Qualitative Study

Abstract: The complexity of cirrhosis requires patients and their caregivers to be well educated to improve outcomes. Data are lacking regarding how to best educate patients and their caregivers in the setting of cirrhosis. Our aim is to understand (both through existing literature and by asking patients and their caregivers) how patients learn about their disease, barriers in their education and disease management, and self‐management strategies. We performed a structured search of published articles in PubMed (1973 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
(48 reference statements)
1
13
0
Order By: Relevance
“…Nutrition is another factor associated with caregiver burden—balancing addressing frailty while adhering to dietary restrictions. Education, especially in this domain, is desired by caregivers, [ 24 ] and its ongoing improvement would be beneficial. Although increasingly common, cirrhosis is rare enough and beset by stigma such that sustainable support groups (online and in person) are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is another factor associated with caregiver burden—balancing addressing frailty while adhering to dietary restrictions. Education, especially in this domain, is desired by caregivers, [ 24 ] and its ongoing improvement would be beneficial. Although increasingly common, cirrhosis is rare enough and beset by stigma such that sustainable support groups (online and in person) are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…To the editor, Patient barriers to self-management in cirrhosis are complex. [1] Although several studies have demonstrated improved knowledge or self-care behaviors following education, [1] long-term outcome data are lacking. We previously reported that a multifaceted pharmacist-led intervention for people with decompensated cirrhosis (including patient-oriented education, medication reconciliation, and identification and resolution of "highrisk" medication-related problems) was associated with fewer unplanned admissions at 12 months compared to usual care (adjusted incidence rate ratio [aIRR], 0.52; 95% confidence interval [CI], 0.30-0.92; p = 0.025).…”
Section: Patient-oriented Medication Education Intervention Has Long-...mentioning
confidence: 99%
“…Lifestyle changes and self-care are essential to disease management. Still, low compliance with prevention and treatment recommendations and inadequate self-care among patients with liver cirrhosis often leads to worse outcomes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%